In-water handwriting in multi-medium using electrical impedance imaging. (21st July 2020) - Wu, Chenning; Soleimani, Manuchehr
Abstract: A novel approach to human–computer interaction, in water handwriting is presented in this work. The novel handwriting method is based on tomographic imaging of electrical resistivity changes. The new method allows the users to write inside of a water ball in a natural, unconstrained way. In-water handwriting suffers no friction and allows handwriting or drawing in a more relaxed way. This work shows how an electrical impedance tomography (EIT) system and sensor/phantom can be used to create a robust handwriting in water. It is well known that EIT has low special resolution but offers a very good functional imaging with high temporal resolution. The work shows an example of a good quality functional imaging aspect of the EIT in a novel human computer interface (HCI) application. Although it is almost impossible to produce images of letters or complex shapes using EIT sensor, it is totally possible to produce the same using many EIT frames. The system used in this study has a frame rate of 15 frames per second so the actual handwriting of letters and shapes can be done without noticing any delays. Analysis of image similarity between actual handwriting and the one follow the EIT scheme shows a good correlation.